Polysaccharides from brown seaweed: Physicochemical properties, absorption in the intestine, and beneficial effects on intestinal barrier - Wanzi Yao; Qiuhong Kong; Lijun You; Saiyi Zhong; Kseniya Hileuskaya (Food Frontiers, 2023)
Abstract The intestinal barrier is critical in maintaining gut homeostasis and host health. The intestinal barrier dysfunction contributes to intestinal and systemic diseases like inflammatory bowel disease, colorectal cancer, and metabolic syndromes. This review summarizes the physicochemical properties of three main kinds of brown seaweed polysaccharides (BSP), laminarin, fucoidan, and alginate, along with their absorption and metabolism in the intestine and their effects on the intestinal barrier. The physicochemical properties of BSP were closely related to their beneficial effects on intestinal health. BSP were not digested directly in the upper gastrointestinal tract but could be utilized through fermentation by the gut microbiota. BSP kept the integrity of intestinal epithelium by ameliorating intestinal oxidative stress through the nuclear factor erythroid 2‐related factor 2 signaling pathway. They also reduced tight junction dysfunction and intestinal permeability and increased the expression of mucins. Moreover, BSP regulated the composition and abundance of gut microbiota and promoted the production of beneficial metabolites such as short‐chain fatty acids. This review will help to understand the gut health‐promoting functions of the natural compounds derived from brown seaweed and offer a new perspective on intestinal disease prevention and therapy with high effectiveness and safety.